2014
DOI: 10.1016/j.parkreldis.2014.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of subthalamic nucleus DBS in Parkinson's disease: From the advanced phase towards the late stage of the disease?

Abstract: Background: Deep Brain Stimulation of the Subthalamic Nucleus (STN-DBS) is an effective treatment for Parkinson's disease (PD), but only few studies investigated its long-term efficacy. Furthermore, little is known about the role of PD-subtype on STN-DBS long-term outcome.Objective: To report the results of a long-term follow-up (mean 11 years, range 10-13) on 26 patients bilaterally implanted in two centres. Methods:Patients were assessed preoperatively and 1, 5 and 11 years after the implant by the Unified P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
170
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(184 citation statements)
references
References 31 publications
10
170
3
1
Order By: Relevance
“…Studies are needed to assess mutation prevalence in subjects with an AAO ≥ 51 years but < 70 years, because DBS is considered in individuals up to age 75 years. 21,23 Also, only patients with MMSE scores > 24 were included in the study; thus, it is possible that mutation carriers who developed dementia after DBS were missed in our cohort. A prospective study is needed to capture the prevalence of mutation carriers in the DBS candidate population and the impact of DBS in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies are needed to assess mutation prevalence in subjects with an AAO ≥ 51 years but < 70 years, because DBS is considered in individuals up to age 75 years. 21,23 Also, only patients with MMSE scores > 24 were included in the study; thus, it is possible that mutation carriers who developed dementia after DBS were missed in our cohort. A prospective study is needed to capture the prevalence of mutation carriers in the DBS candidate population and the impact of DBS in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The most common side effects are speech problems (hypophonia, dysarthria) and dystonias (in particular, blepharospasm and eyelid opening apraxia). Others, such as freezing or unsteadiness of gait, or weight gain, are the result of chronic stimulation and disease progression [57]. Adaptive DBS may be the most promising approach to reduce the incidence of these problems.…”
Section: Stn Imaging and Target Selectionmentioning
confidence: 99%
“…In addition, transitioning image acquisition from the pre-operative phase and into the operating room is already promising to fundamentally change DBS surgery by allowing real-time targeting which may eventually obviate the need for extensive intraoperative physiological mapping. This will, in turn, lead to a decrease in operative time and the associated morbidity [57]. Indeed, targeting based solely on image guidance has become routine practice in some centers [51,61].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
“…Studies have demonstrated a notable improvement in quality of life, motor scores, and a reduction of wearing off in patients who have received DBS [17,18,19]. Overall benefits have been maintained for up to 11 years according to long-term follow-up studies [20,21,22] although there is some concern that any initial benefit in gait or posture may deteriorate more quickly [23]. …”
Section: Parkinson’s Diseasementioning
confidence: 99%